PENGARUH PELATIHAN KETRAMPILAN PEMBUATAN SEPATU SECARA MANDIRI TERHADAP PENINGKATAN TARAF HIDUP BURUH PABRIK SEPATU - Yeni Firmawati; Winanti . (Journal Of Communication Education, 2014)
AbstractThe study was conducted using random sampling method , with a population of 2,000 respondentsand the amount of samples taken by 200 respondents ( 10 % of total population ) .After training researchers evaluated how much influence skills training on improving the livingstandard of workers . From the research, the researcher makes the analysis serve as the research andcompiled in a report in the form of research reports . There is a significant effect of training on theirown shoe-making skills to the level of standard of living of workers , although the results of thecomparison between the calculated F and F tables are very small level of significance . T value onskills-training shoes is 1,709 , the degrees of freedom ( df ) = N - 2 = 200-2 = 198 , t value table at thelevel of 95 % ( 5 % significance ) is 1.645 so that t is greater than t table , it was decided that asignificant regression coefficient , or shoe-making skills training independently affect the level ofworkers' standard of living significantly at 95% confidence level.Keywords : influence, training, skill, Pelatihan Ketrampilan, standard of living